Utilização de materiais naturais como medida de produção mais limpa no isolamento térmico de coletor solar para aquecimento de água - Santor, Cilione Gracieli (2012)
Development without harming the environment is a growing concern and clean sources of energy emerges as one of the main contributors for a sustainable world. Solar thermal energy is becoming ubiquitous and has increased its participation in the energy matrix. The construction of this kind of equipment has targeted mainly in the gain of efficiency, but researches must focus also on the use of environmentally friendly materials and low environmental impact. This research aimed to develop a thermal insulating plate from natural materials and compare its dynamic performance with glass wool insulation. Sunflower stalk, rice husk, jute fiber and gypsum were mixed to form an insulating plate. Action research method, with improvement cycles, was used to develop and implement a natural composite plate. The results showed that the insulating plate exhibits behavior similar to that of glass wool when subjected to the daily cycles of a low temperature solar thermal system. The developed plate can be considered feasible in technical and environmental point of view. Good mechanical strength and thermal conductivity comparable to glass wool was achieved. All components of the composite are natural material without any waste of raw material or in the process. There is no need of large amounts of energy. However, its economic viability requires further study.